Causes and Patterns of Dental Extraction in Dental College of Sebha University - Abdusalam A Milad, Milad; E.E. Ibrahim, Abdulsalam; Glewan Mohamed, Ahmed (Libyan Journal of Dentistry, 2024)
Objectives: This study aimed to identify the primary cause of permanent teeth extraction among patients attending the Oral and Maxillofacial Surgery (OMFS) department of dental college, Sebha University, and its correlation with age, gender, and tooth type. Methods: A cross-sectional study was conducted over ten months; and included 509 patients aged 16-90 years, who underwent tooth extraction. Variables studied were the patient's age, gender, tooth type, and extraction cause. SPSS was used for data analysis, and Chi-Square and ANOVA tests were used to evaluate variables associated with the cause of tooth loss. A p-value of less than 0.05 was considered statistically significant. Results: Overall, 509 permanent teeth were extracted, males (62.1%) and females (37.9%). The primary reasons for tooth extraction were dental caries (76.62%), mobility (10.80%), prosthodontics (6.86%), orthodontics, and impaction (2.95%). The most common age group was 36-45 years (24.36%) and 26-35 years (23.38%). The highest percentage of tooth extraction was in the third and first molars (29.1% and 24.4%, respectively), and the lateral incisor (1.77%) was the lowest. There was an insignificant association between the cause of extraction and gender; a significant association between the cause of extraction and age p<0.001; and a significant association between (gender and age) with tooth type p< 0.001. Conclusion: dental caries was the main reason for tooth extraction in OMFS department, dental college, Sabha University.